Políticas de incentivo a escola melhoram a proficiência no ensino fundamental ? uma avaliação do prêmio escola nota dez - Carneiro, Diego Rafael Fonseca (2015)
The Escola Nota Dez award aims to support municipalities of Ceará on improving their basic education system through the distribution of financial bonuses the schools whose students of elementary school achieve specific scores Permanent Evaluation System of Basic Education Ceará (SPAECE). Thus, this work has as its objective to evaluate the impact of incentive program in the performance of schools. Based on the ratings of Portuguese and Mathematics of the Prova Brasil 2007 and 2011 comparing the performance of beneficiary and non-beneficiary of Ceará schools before and after the award by the difference in differences model. From the results, it can be said that the Award has a positive effect on the average proficiency of the winning schools compared to non-rewarded. In addition, the schools supported by Award show equivalent performance to schools not winning, which indicates an improvement in performance, considering that to be supported schools should be among the 150 worst performing in literacy.